Measurement instruments for the core outcome set of congenital melanocytic naevi and an assessment of the measurement properties according to COSMIN: a systematic review. (March 2023) - Fledderus, A.C.; Boom, T.; Legemate, C.M.; van der Horst, C.M.A.M.; Spuls, P.I.
Abstract: Background: Congenital melanocytic naevi (CMN) can impact on patients' lives due to their appearance and the risk they carry of neurological complications or melanoma development. The development of a core outcome set (COS) will allow standardised reporting and enable comparison of outcomes. This will help to improve guidelines. In previous research, relevant stakeholders reached a consensus over which core outcomes should be measured in any future care or research. The next step of the COS development is to select the appropriate measurement instruments. Aim: Step 1: to update a systematic review identifying all core outcomes and measurement instruments available for CMN. Step 2: to evaluate the measurement properties of the instruments for the core outcomes. Methods: This study was registered in PROSPERO and performed according to the PRISMA checklist. Step 1 includes a literature search in EMBASE (Ovid), PubMed and the Cochrane Library to identify core outcomes and instruments previously used in research of CMN. Step 2 yields a systematic search for studies on the measurement properties of instruments that were either developed or validated for CMN, including a methodological quality assessment following the COSMIN methodology. Results: Step 1 included twenty-nine studies. Step 2 yielded two studies, investigating two quality of life measurement instruments. Conclusion: Step 1 provided an overview of outcomes and instruments used for CMN. Step 2 showed that additional research on measurement properties is needed to evaluate which instruments can be used for the COS of CMN. This study informs the instrument selection and/or development of new instruments.